PERANCANGAN ULANG TATA LETAK FASILITAS DENGAN PENDEKATAN LEAN MANUFACTURING - Prasetya, Alexander; Noya, Sunday Alexander Theophilus (Universitas Muhammadiyah Surakarta, 2015)
One of the big investment in a business is facility design. It is a long-term investment due to great value. In its development, PT. Dwi Putra Sakti faced some problems related to facility layout. Problems that can be identified, such as work in process that has accumulated on the production floor, as well as the anorganizad facility layout. Therefore, it is necessary to redesign the layout for the production process more effective and efficient. This study uses a lean manufacturing approach to redesign facility layout. It used value stream mapping, seven waste, cellular manufacturing and 5S principle. Analysis of the implementation result is used to design the layout of the new facility. Level layout that will be examined are the macro-and micro-layout layout. Results of macro-layout design is decreasing production cycle time of trousers. While the micro-layout design is decreasing in material handling displacement.